TRANSLATION ANALYSIS OF MATERIAL CULTURE TERMS FOUND IN VIDEO GAME ENTITLED CITAMPI STORIES - Allfine Ary Kurniawan (Haluan Sastra Budaya, 2022)
This article analyzed Indonesian material culture terms found in video game entitled “Citampi Stories”. The objectives are to classify the material culture term categories, to identify the translation techniques used and to assess the accuracy of the translation. The study is a qualitative descriptive study, designed to be single-embedded case study and product oriented study. Results shows that there are four categories of material culture terms found in game, which are foods, clothes, houses and towns, and artifacts. In addition, the analysis shows that six translation techniques are used; they are adaptation, borrowing, discursive creation, established equivalence, generalization and literal translation; and then, the accuracy assessment result explains that the translation of Indonesian material culture terms in “Citampi Stories” are less accurate, resulted in an average score of 2.05.